Cognitive complexity metrics and its impact on software reliability based on cognitive software development model. - Singh Kushwaha, Dharmender (Software engineering notes.)
Software metrics provide a quantitative basis for the development and validation of models of software development process. Information gained from metrics is used in managing the development process in order to improve the reliability and quality of software product. The software metric is used to estimate various parameters of software development lifecycle such as cost, schedule productivity, quality and reliability. In this paper, an attempt has been made to frame the cognitive complexity metrics that will aid in increasing the reliability of software product being developed during the development lifecycle.